Linking local knowledge, conservation practices and ecosystem diversity: comparing two communities in the Tunari National Park (Bolivia) - Boillat, Sébastien; Mathez-Stiefel, Sarah-Lan; Rist, Stephan (Ethnobiology and Conservation, 2013)
Combined approaches to conserve both biological and cultural diversity are seen as an alternative to classical nature conservation instruments. The objective of this study was to examine the influence of urbanization coupled with exclusive conservation measures, on land use, local knowledge and biodiversity in two Quechua speaking communities of Bolivia located within the Tunari National Park. We assessed and compared the links between land use, its transformation through conservation practices, local institutions and the worldviews of both communities and the implications they have for biodiversity at the level of ecosystems. Our results show that in both communities, people’s worldviews and environmental knowledge are linked with an integral and diversified use of their territory. However, the community most affected by urbanization and protected area regulations has intensified agriculture in a small area and has abandoned the use of large areas. This was accompanied by a loss of local environmental knowledge and a decrease in the diversity of ecosystems. The second community, where the park was not enforced, continues to manage their territory as a material expression of local environmental knowledge, while adopting community-based conservation measures with external support. Our findings highlight a case in which urbanization coupled with exclusive conservation approaches affects the components of both cultural and biological diversity. Actions that aim to enhance biocultural diversity in this context should therefore address the impact of factors identified as responsible for change in integrated social-ecological systems.